Peningkatan Pengetahuan Melalui Pendidikan Kesehatan Hidup Sehat Mencegah Komplikasi Diabetes Di Kelompok Prolanis “SEHATI” Puskesmas Nganjuk: Increasing Knowledge Through Health Education Healthy Living Prevents Diabetes Complications in the Prolanis "SEHATI" Group of Nganjuk Community Health Center - Purwandari, Henny; Suhita, Byba Melda (Jurnal Abdi Keperawatan dan Kedokteran, 2023)
Prevention and control of non-communicable diseases aims to improve the quality of life of people with non-communicable diseases so that they are able to be independent in treating their illnesses and prevent complications. In diabetics, many primary, secondary and tertiary prevention efforts have been implemented, but there are still obstacles in implementing the program, one of which is due to the lack of public awareness in complying with the management of predetermined treatment programs. The chronic disease management program implemented by the government aims to encourage people participating in the National Health Insurance Card to be healthy, especially for hypertension and diabetes, so they can achieve optimal quality of life and prevent complications. Prolanis is a health service system that is carried out with a proactive approach in an integrated manner involving participants, health facilities in the framework of health maintenance. This Community Service activity was carried out by providing health education to the "Sehati" Prolanis group at the Nganjuk Health Center with a target of 60 members of the same heart prolanis group with Healthy Living material preventing Diabetes complications. The method used in this activity is through presentation of material, question and answer and discussion as well as giving a questionnaire to assess the knowledge of people with diabetes. The results obtained from the Health Education carried out were that there was an increase in the knowledge of the prolanis participants by 30% for the good category, for the sufficient category of knowledge, it decreased by 16.7% and for the less category, it decreased by 13.3%. Health education activities in the prolanis group received full support from program managers and high enthusiasm from the prolanis group participants to increase knowledge and prevent complications in diabetes.